Factors associated with suicidal ideation in the French nationwide EPICOV study - C. Davisse-Paturet; M. Orri; A.-M. Florence; J.-B. Hazo; M.-C. Geoffroy; M. Melchior; A. Rouquette (European Psychiatry, 2022)
Introduction The COVID-19 pandemic seems associated with a worsening in mental health issues as well as a widening of pre-existing social and health inequalities. Assessment of its impact on suicidal behavior might therefore be relevant.